The Research on Technology in Arabic Language Learning: A Bibliometric Analysis (1993-2024) - Muhammad Hafidz Khusnadin; Dwi Arian Putra Mandaka; ⁠Zulfi Fadhlurrahman; ⁠Zaeni Anwar; Ramadhan Safrudin (Center of Language and Cultural Studies, 2024)
This study aims to analyze research trends related to the use of technology in Arabic language learning from 1993 to 2024 using bibliometric analysis methods. The research data was obtained from the Scopus database, and through data processing, the authors identified 100 relevant publications. The bibliometric analysis revealed that 2023 had the highest number of publications, with 21 articles related to the use of technology in Arabic language learning. Furthermore, a significant citation trend associated with this topic occurred in 2022, with a total of 135 citations in scientific literature. Regarding the origin of the research, Malaysia emerged as the leading contributor with 24 related publications, while Saudi Arabia stood out as the country with the most significant international collaboration, with 23 collaborative links with other countries. Of all the journals that published this research, 26 were classified as Q1 journals, indicating a high level of relevance and impact of this research in the scientific literature. A deeper analysis revealed that the focus of research related to the use of technology in Arabic language learning encompasses four main aspects: 1) Deep Learning and e-learning; 2) Speech recognition; 3) Learning systems and machine learning; 4) Natural language processing. This study provides a comprehensive insight into the research trends and developments in the use of technology in the context of Arabic language learning over the past two decades.